Education and Safety in Construction - Alfredo Soeiro (1996)
The module of construction safety is included in a general course about methods and technologies of construction. It is actually divided in four parts. The first component of the module aims at giving an overview of the number and type of accidents in Portugal and in the European Union. The second part is dedicated to present the current regulations concerning safety in the area of construction. The third phase is a general survey about the economic consequences of accidents motivated by the irregularities committed against legal requirements. The fourth part is a practical exercise based on simulation using a cause-effect preocedure.